1996
DOI: 10.1177/030089169608200505
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Survival and Age at Diagnosis of Women with Breast Cancer from a Population-Based Study in Umbria, Italy

Abstract: We analyzed the 10-year survival of 1,512 women with breast cancer in relation to age at diagnosis. The incident cases were from an ad hoc investigation in Umbria, a region of central Italy, for the period 1978-1982. The follow-up was carried out by an automatic link with the RENCAM (Nominative register of causes of death) and verified at the Registrar's Offices of the various towns of the region. Observed survival at 1 year was 0.89, at 3 years 0.75, at 5 years 0.64 and at 10 years 0.47. Median survival was 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, whether young age is a hallmark of poor prognosis remains controversial [1,4]. Many studies revealed obvious survival differences between young and elderly breast cancer patients [2,5], but other studies concluded that young age had no impact on [6][7][8] or even improved the prognosis [4,9]. Breast cancer is one of the most common cancers in Chinese women, and its incidence is increasing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether young age is a hallmark of poor prognosis remains controversial [1,4]. Many studies revealed obvious survival differences between young and elderly breast cancer patients [2,5], but other studies concluded that young age had no impact on [6][7][8] or even improved the prognosis [4,9]. Breast cancer is one of the most common cancers in Chinese women, and its incidence is increasing.…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analysis in some studies revealed survival differences in patients with hormone receptor-positive tumors, but no differences in those with hormone receptornegative tumors [12,23]. However, some studies concluded that young age had no impact on [6,8] or even improved the prognosis [4,9]. The inconsistent results from different studies can be explained by the following factors: relatively smaller sample sizes of very young patients included; inconsistent age ranges for control groups in different studies although the cutoff value for age at diagnosis was 35 years in most studies; changes in therapy strategies during study inclusion due to long time intervals for inclusion; possible heterogeneities among different races and different treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Histology was found to be prognostic in breast cancer. Lobular cancer had a better prognosis than ductal cancer for separate or combined stages [ 11 ]. Mclaughlin et al reported that lobular cancer had a better prognosis than ductal cancer for combined stages [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have revealed that age is not related to overall or disease-free survival after adjustment for other prognostic variables [ 8 , 9 ]. Several authors have even reported that young patients have better survival [ 10 , 11 ]. In addition, data on treatment effects are largely dependent upon older series collected over several years and extrapolation of data from older age cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, significant differences in study designs have resulted in a lack of consensus regarding the prognostic effect of patient age. La- Rosa et al (1996) observed that women less than 35 years had a better prognosis at 5 years from diagnosis. Holli and Isola (1997) found that the 5-year RSR was highest in women aged 46 -50 years, whereas they found no significant difference between younger and older age groups.…”
Section: Discussionmentioning
confidence: 99%